A genetic algorithm for symmetric travelling salesman problem eith due dates - Lee, Lai Soon; Potts, Christopher N.; Bennell, Julia A. (2007)
A new symmetric version of the time constrained traveling salesman problem is introduced, where cities to be visited have due dates. The objective is to find an ordering of the cities that starts and ends at the depot which minimises the maximum lateness, and the total tour length of the cities. A genetic algorithm (GA) which utilizes the multicrossover operator is developed. We introduce a subtour based crossover where the constraint on sharing the common subtours in both parents is relaxed. Computational results of the proposed GA compared to other local search methods are presented.